Sustainable iridescence of cast and shear coatings of cellulose nanocrystals. (1st December 2021) - Guo, Mengna; Li, Yu; Yan, Xueyi; Song, Jianing; Liu, Dagang; Li, Qin; Su, Fan; Shi, Xingwei
Abstract: As an eco-friendly sustainable iridescent coating, cholesteric cellulose nanocrystal (CNC) is susceptible to substrate effects or shearing effects. In this work, interface interaction and liquid crystal phase transition were evaluated for fabricating iridescent cast or shear coatings of CNCs onto substrates of polystyrene, glass, ceramic, wood, stainless steel, metal, or metal alloy. Three types of substrate effects and four categories of shearing effects on the structure color mechanism of CNC coatings were proposed. Practically, several efficient approaches, such as increasing colloidal concentration, enhancing water-retention of substrates, raising processing temperature, slowing down shearing speed, or doping functional additives were involved. Hence, a feasible strategy was provided for preparing sustainable, iridescent, stable, and industrially scalable coatings of CNCs. Graphical abstract: Unlabelled Image Highlights: Three categories of cast coatings are proposed according to substrate effects. Substrate effects are settled by rising cast temperature, or water-retention of substrate. Shearing effects are addressed by rising dope concentration or reducing painting speed. Preserving cholesteric phases is the key of sustainable vivid iridescence of CNC coatings.